2019
DOI: 10.22436/jnsa.013.03.03
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic roots of a second order retarded functional differential equation via spectral-tau method

Abstract: In this paper, we have found the solution of second-order delay differential equations of retarded type with multiple delays. As well as developing an approximation for finding characteristic roots for such delay differential equations via the method of spectral tau which depends on the basis mixed Fourier basis or shifted Chebyshev polynomials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Recently, Abdullah and et al found analytical solutions of retarded dynamical systems of the third order and of the n th order by using Lambert W function and a discussion of their stability in their two papers (7)(8) respectively. Abdullah and et al found approximate characteristic roots for DDEs with multiple delays via the method of spectral tau (9).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Abdullah and et al found analytical solutions of retarded dynamical systems of the third order and of the n th order by using Lambert W function and a discussion of their stability in their two papers (7)(8) respectively. Abdullah and et al found approximate characteristic roots for DDEs with multiple delays via the method of spectral tau (9).…”
Section: Introductionmentioning
confidence: 99%